2022
DOI: 10.1007/s11356-022-18902-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Persea americana fruit and seed extracts against chemically induced liver cancer in rats by enhancing their antioxidant, anti-inflammatory, and apoptotic activities

Abstract: This study aims to explore the chemopreventive mechanisms of hydroethanolic extracts from avocado (Persea Americana) in diethylnitrosamine (DEN)/2-acetylaminofluorene (2AAF)-induced hepatocarcinogenesis. Chemical induction of hepatocarcinogenesis was induced by intraperitoneal injection of DEN at 150 mg/kg body weight (b.w.) twice a week for a fortnight, followed by oral administration of 2AAF at 20 mg/kg b.w. four times a week for 3 weeks. Rats administered DEN/2AAF were orally treated with hydroethanolic ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 68 publications
6
8
1
Order By: Relevance
“…Oxidative stress, inflammation, and apoptosis suppression by treatments with rutin and quercetin attribute to the amelioration of liver function and structural integrity (Scheme 2). The present investigation found that DXR-injected animals exhibited elevated levels of serum total bilirubin, which is similar with the results of Liss et al [70], Ahmed [71], Hozayen et al [60], Hassan et al [67], Ahmed et al [68], and Ahmed et al [72]. These researchers argued that it is a clear indicator of liver disease and may be caused by bile ductile occlusion induced by portal triad inflammation and fibrosis and/or conjugated bilirubin reflux from necrotic hepatocytes to sinusoids.…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative stress, inflammation, and apoptosis suppression by treatments with rutin and quercetin attribute to the amelioration of liver function and structural integrity (Scheme 2). The present investigation found that DXR-injected animals exhibited elevated levels of serum total bilirubin, which is similar with the results of Liss et al [70], Ahmed [71], Hozayen et al [60], Hassan et al [67], Ahmed et al [68], and Ahmed et al [72]. These researchers argued that it is a clear indicator of liver disease and may be caused by bile ductile occlusion induced by portal triad inflammation and fibrosis and/or conjugated bilirubin reflux from necrotic hepatocytes to sinusoids.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, both proteins increased significantly in NAPAP-administered rats and the treatment with MPHE, hesperidin, and quercetin significantly reduced these NAPAP-induced elevations reflecting the antiapoptotic effects of MPHE, hesperidin, and quercetin (Figure 8). It is worth mentioning that p53 is an important mediator of intrinsic apoptosis [123,124], and the activation of caspase 3 can be mediated by stimulation of both intrinsic and extrinsic pathways of apoptosis [36]. Moreover, TNF-α may activate the extrinsic pathway by binding to tumor necrosis factor receptors (TNFR) on the cell membrane [36] (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…The lungs are the most vulnerable organ for endogenous oxidants and ROS damage because they interact with the outside environment [ 35 ]. In experimental animals, DENA is a common and widely used chemical substance to induce esophageal, hepatic, and pulmonary malignancies [ 7 , 36 ]. In this study, we evaluated the chemopreventive effect of eugenol on DENA/AAF-induced lung cancer and determined its possible action mechanisms.…”
Section: Discussionmentioning
confidence: 99%